Environmental science : - Cunningham, William P. (McGraw-Hill, 2007)
Environmental Science, Ninth Edition, is a comprehensive presentation of environmental science for non-science majors which emphasizes critical thinking, environmental responsibility, and global awareness. This book is intended for use in a one- or two-semester course in environmental science, human ecology, or environmental studies at the college or advanced placement high school level. The goal of this book is to provide an up-to-date, introductory global view of essential themes in environmental science along with emphasis on details and case studies that will help students process and retain the general principles. Because most students who will use this book are freshman or sophomore non-science majors, the authors make the text readable and accessible without technical jargon or a presumption of prior science background. At the same time, enough data and depth are presented to make this book suitable for many upper-division classes and a valuable resource for students who will keep it in their personal libraries after their formal studies are completed.